Superhydrophobic Vertically Aligned Carbon Nanotubes for Biomimetic Air Retention under Water (Salvinia Effect). Issue 13 (10th May 2017) - Babu, Deepu J.; Mail, Matthias; Barthlott, Wilhelm; Schneider, Jörg J.
Abstract : The Salvinia effect refers to the stable retention of an air layer when submerged in water and is a result of complex hierarchical structuring, ultimate example of which is the surface of the floating fern Salvinia molesta . The air retention capability is technologically interesting as the retained air layer reduces drag force, prevents biofouling, and serves sensory functions. Air retention on artificial materials is currently limited to very few materials and is often a result of micrometer sized surface structures obtained by complex lithography techniques. In the present work, the air retention capabilities of superhydrophobic vertically aligned carbon nanotubes (VACNTs) are explored for the first time and the retained air layer is characterized by atomic force microscopy and confocal microscopy techniques. While the as‐prepared VACNTs retained only small pockets of air when submerged in water, superhydrophobic and regrown VACNT structures are found to be capable of retaining a continuous thick layer over extended period of time. The stable air retention capabilities of these nanostructured VACNT surfaces hold promising pathways for the development of biomimetic sensor systems. Abstract : Semiaquatic plants have developed the ability to retain a layer of air when submerged in water, a supreme example is the complex surface of the floating fern Salvinia molesta . For the first time, the Salvinia effect is reported in an all carbon based architecture, vertically aligned carbon nanotubes. This effect opens promising pathways for the development of artificial biomimetic sensors.